Interleukin-6 Level and Neutrophil-Lymphocytes Ratio and Severity of Coronavirus Disease 19 - Latifah, Armina; Parwati, Ida; Tjandrawati, Anna; Suraya, Nida (Majalah Kedokteran Bandung, 2024)
Interleukin-6 (IL-6) is a proinflammatory cytokine that plays an important role in hyperinflammation and cytokine storm in Coronavirus Disease 19 (COVID-19) patients. The neutrophil-lymphocyte ratio (NRL) describes the innate and adaptive immune responses. Elevated IL-6 and NLR levels usually indicate a severe clinical condition in COVID-19 patients. Aim of this study was to determine the correlation of IL-6 and NLR with the severity of illness in COVID-19 hospitalized patients. This was a descriptive correlative observational study with a cross-sectional design using secondary data from COVID-19 patients treated in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, from November 2020 to October 2021. There were 225 subjects who were classified by the severity and analyzed for IL-6 levels and NLR. Median levels of IL-6 at moderate, severe, and critical levels were 4.1 pg/mL, 20.4 pg/mL, and 38.8 pg/mL, respectively. The median NLR at moderate, severe, and critical grades were respectively 4.41, 9.65, and 17.79. The correlation between IL-6, NLR, and severity was 0.441 (p<0.001) and 0.408 (p<0.001). Meanwhile, the correlation between IL-6 levels and NLR in COVID-19 was 0.230 (p<0.001). Thus, IL-6 and NRL levels have a moderate positive correlation with the severity of COVID-19, while IL-6 and NRL have a weak correlation because IL-6 is not the only factor that affects the NRL.